Analyzing the response of submerged arc welding process parameters on Form factor and dilution. (2022) - Mohal, Sachin; Chaitanya, Saurabh; Singh, Manjit; Goyal, Rachin; Kumar, Amresh; Saini, Gaurav
Abstract: Stainless steel (316) possesses higher strength to weight ratio, high toughness and high tensile strength. It has wide range of applications in fabrication of heat exchangers, boat fittings as wire rope clips, in making of tanks, springs and screws, Medical implants, Sinks and splash backs. Welding of these materials has always been a challenging task. Submerged arc welding due to its various properties and specification has been found suitable for this type of work. In this research work, weld bead geometry parameters; Dilution, Form Factor were optimized by using Response Surface Methodology (RSM). Welding current has been found to be the most crucial parameter among all the selected parameters.